Climate Change and Health Impacts : How Vulnerable is Bangladesh and What Needs to be Done? - Mani, Muthukumara S.; Limin Wang (World Bank, Washington, DC, 2015)
This study was jointly undertaken by the Climate Change and Health Promotion Unit of the Ministry of Health and Family Welfare, the International Centre for Diarrheal Disease Research, Bangladesh, and the World Bank. This study had two broad objectives: (1) to assess national vulnerability and impact on major diseases of increased climate variability and extreme events in Bangladesh; and (2) to assess existing institutional and implementation capacity, financial resources at the local level, and existing public programs targeted at climate-sensitive diseases.